Analysis of Sanitation Facilities and Implementation of Health Protocols in Pasar Baru District, Pangkalan Kerinci, Pelalawan Regency During the Covid-19 Pandemic in 2022: Analisis Sarana Sanitasi Dan Penerapan Protokol Kesehatan Di Pasar Baru Kecamatan Pangkalan Kerinci Kabupaten Pelalawan Pada Masa Pandemi Covid-19 Tahun 2022 - Nurul Fitri; Riri Maharani; Ikhtiyaruddin Ikh; Emy Leonita; Denai Wahyuni (Badnur Medisa Group, 2022)
COVID-19 is an infectious disease that attacks the respiratory tract caused by the corona virus (novel coronavirus). COVID-19 cases in Pelalawan Regency, Riau Province as of January 11, 2022, were 3,432 positive confirmed cases, with 182 deaths. Based on the results of the researchers' first observations that sanitation facilities are not optimal and the application of health protocols has not been implemented. The purpose of this study is to analyze sanitation facilities and the application of health protocols in Pasar Baru, Pangkalan Kerinci District, Pelalawan Regency during the 2022 covid-19 pandemic. The method used in this research is analytical qualitative. The informants of this study were 7 peoples using purposive sampling technique. Data collection was done through in-depth interviews and observation. The results of this study are the availability of hand washing facilities that do not meet the requirements, disinfection facilities have not been implemented optimally, generally sellers and buyers have not implemented the use of masks, hand washing with soap has not been applied optimally, physical distancing has not been implemented in Pasar Baru, currently avoiding crowds is not implemented by sellers and buyers, and the implementation of reducing mobility has not been implemented in Pasar Baru. It is hoped that the manager of Pasar Baru will complete the provision of sanitation facilities that are not yet optimal and collaborate regularly with the authorities to conduct raids again regarding the implementation of health protocols in Pasar Baru